Precalculus : algebraic and trigonometric functions, vol. 7 : Trigonometric ratios. (San Rafael, California : Individual Learning Systems, Inc., 1971)
In unit nine you will learn to identify the amplitude, period, and shift of sine and cosine functions and use these values to sketch the graphs of the functions. You will work with additional identities involving the sine and cosine ratios as well as other trigonometric ratios.
Unit Nine: Trigonometric Ratios -- Module 32. Sine and Cosine Identities -- Module 33. Trigonometric Identities and Equations -- Module 34. Complex Numbers in trigonometric Form.
Keywords: PRECALCULUS -- SINE -- COSINE -- TRIGONOMETRIC RATIOS